Parkin Sensitizes toward Apoptosis Induced by Mitochondrial Depolarization through Promoting Degradation of Mcl-1 - MARTIN, SEAMUS (My University, 2014)
Mitochondrial depolarization promotes Parkin- and PTEN-induced kinase 1 (PINK1)-dependent polyubiquitination of multiple proteins on mitochondrial outer membranes, resulting in the removal of defective mitochondria via mitophagy. Because Parkin mutations occur in Parkinson’s disease, a condition associated with the death of dopaminergic neurons in the midbrain, wild-type Parkin is thought to promote neuronal survival. However, here we show that wild-type Parkin greatly sensitized toward apoptosis induced by mitochondrial depolarization but not by proapoptotic stimuli that failed to activate Parkin. Parkin-dependent apoptosis required PINK1 and was efficiently blocked by prosurvival members of the Bcl-2 family or knockdown of Bax and Bak. Upon mitochondrial depolarization, the Bcl-2 family member Mcl-1 underwent rapid Parkin- and PINK1-dependent polyubiquitination and degradation, which sensitized toward apoptosis via opening of the Bax/Bak channel. These data suggest that similar to other sensors of cell stress, such as p53, depending on the degree of mitochondrial damage.
PUBLISHED
Keywords: Parkin has cytoprotective (mitophagy) or cytotoxic modes (apoptosis); Parkin has cytoprotective (mitophagy) or cytotoxic modes (apoptosis)